Glucagon-like peptide1 receptor agonist treatment of cystic fibrosis-related diabetes complicated by obesity: A cases series and literature review - Ammar Ahmed; Anvitha Ankireddypalli; Tasma Harindhanavudhi; Antoinette Moran; Amir Moheet (Journal of Clinical & Translational Endocrinology)
Cystic fibrosis-related diabetes (CFRD) is the most common non-pulmonary comorbidity in people with cystic fibrosis (CF). Current guidelines recommend insulin therapy as the treatment of choice for people with CFRD. In the past, obesity and overweight were uncommon in individuals with CF. However, in recent years, advancements in CF therapies have led to a significant increase in the prevalence of overweight and obesity within this population. Glucagon-like peptide1 receptor agonist (GLP-1 RA) therapies could potentially improve glycemic control in people with CF by increasing insulin secretion, slowing gastric emptying, and promoting weight loss through central appetite suppression, which in turn can enhance insulin sensitivity. We report, for the first time, five cases of individuals with CFRD complicated by obesity treated with GLP 1-RA for at least two years. With GLP 1-RA therapy, 4 out of 5 individuals exhibited weight reduction ranging from 7% to 19% over two years, while forced expiratory volume in 1 s (FEV1)/predicted FEV1 % remained stable or improved in all cases. The impact on glycemic control was variable. Insulin requirements either reduced or remained stable in all five cases. Overall, GLP-1 RA was well tolerated in this case series; one individual discontinued the medication after two years of therapy due to poor appetite and nausea.